Actor engagement valence: Conceptual foundations, propositions and research directions. (4th May 2018) - Li, Loic Pengtao; Juric, Biljana; Brodie, Roderick J.
Abstract : Purpose: Valence is one of the key dimensions underlying actor engagement, yet there is limited research to provide a comprehensive understanding of the concept. The purpose of this paper is to conceptualise engagement valence in actor networks and develop an agenda for future research. Design/methodology/approach: The exploration of the psychological foundations of the concept of valence and a systematic literature review from a multiple database search contribute to four sets of propositions defining the domain of the concept of actor engagement valence. Findings: The propositions posit that valence resides in the engaging actor's past, current and future psychological dispositions, which can shift between positive, negative and ambivalence. Actor engagement valence is triggered by the engagement objects and value propositions of other actors in the network. The antecedents of actor engagement valence comprise individual factors such as cognitive evaluations and hedonic feelings, as well as network-related factors such as social norms and shared beliefs, and the network structure. The net balance of actor engagement valence determines the actor's engagement behaviours, and this relationship is moderated by individual and network factors. Originality/value: This is the first study to conceptualise actor engagement valence, which contributes to the refinement of the actor engagement concept. This research defines the conceptual domain, deepens the understanding and provides an agenda for future research into the valence of engagement among actors in networks. The study recognises the institutional influences on actor engagement valence, and contributes to an understanding of the nature of actors' psychological dispositions and how their valence determines the actors' behavioural engagement manifestations.